A Pollen Analytical Investigation of a Bronze Age and Pre-Roman Iron Age Soil Profile from Grøntoft, Western Jutland - Vad, Bent (Journal of Danish Archaeology, 1985)
A Pollen Analytical Investigation of a Bronze Age and Pre-Roman Iron Age Soil Profile from Grøntoft, Western Jutland